(untitled) (Lafia Journal of Scientific and Industrial Research, 2025)
Background: Candida albicans is a common fungal pathogen that affects women during pregnancy due to hormonal and immunological changes. This study aimed to determine the prevalence of Candida spp. among pregnant and non-pregnant women attending the gynaecology clinic at Dalhatu Araf Specialist Hospital (DASH) Lafia. Methods: A total of 100 women (50 pregnant and 50 non-pregnant) were examined for Candida albicans colonization. Samples of high vaginal swabs (HVS) were collected from both pregnant and non-pregnant women. The samples were cultured on Sabouraud Dextrose Agar (SDA) and ChromaAgar, the isolates were examined microscopically after Gram staining, and presumptively identified by germ tube testing and confirmed by sugar fermentation test and incubation at 45°C after subculturing. Data were analyzed using the chi-square test to determine statistical significance. Results: The overall prevalence of Candida albicans was 64%. Pregnant women had a higher prevalence (72.0%) compared to non-pregnant women (56.0%) (χ² = 4.32, df = 1, p = 0.038). Age-related analysis showed that the highest prevalence was among pregnant women aged 26–35 years (80.0%), while younger women (18–25 years) had comparable prevalence rates regardless of pregnancy status. The chi-square test for age-related prevalence indicated a significant association (χ² = 17.23; p < 0.001). Conclusion: Pregnancy increases the risk of Candida albicans colonization among women aged 26–35 years. Routine screening and preventive measures should be emphasized, especially in high-risk groups.